Effects of photo-selective netting in Summer Beefsteak Tomato (Solanum lycopersicum L.) cultivation on the environmental conditions under nets as well as growth and yield - Kuei-Yuan Chang; Jun-Cheng Dai; Yu Sung (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
Located in a subtropical zone, Taiwan has intense summer sunlight that affects beefsteak tomato cultivation. In this study, beefsteak tomatoes were grown net-house under photo-selective netting of different colors to investigate netting performance. A significantly higher photosynthetic photon flux density (PPFD) was observed under the 24-mesh white (W24) and 24-mesh pink (H24) netting. A difference between the four net-house was only observed for wavelengths of 500-599nm. In 32-mesh blue (B32), the red to blue (R/B) and red to far-red (R/FR) ratios were significantly lower across canopies. The photosynthetic capacity of photosystem II of leaves in W24 was the lowest among the four treatments. In all four, fruit growth was relatively low under the impact of high temperatures, with the lowest single fruit weight and the smallest number of fruits per plant observed in W24. In H24 and 24-mesh pink (HH24), the yield per plant was significantly higher. Significantly fewer whiteflies were observed in the netting houses in H24, HH24, and B32 than in W24. However, the netting still failed to prevent high temperatures at noon. In H24 and HH24, the amount of light retained in the canopies was greater, the photosynthesis capacity was unchanged, the fruit yield was greater and the number of whiteflies in the netting houses was significantly lower. Therefore, pink netting is recommended for beefsteak tomato cultivation.